Endogenous Fusarium Endophthalmitis in Diabetes Mellitus - S. Balamurugan; Ashish Khodifad (Case Reports in Ophthalmological Medicine)
Endogenous endophthalmitis accounts for 2% to 8% of cases of endophthalmitis. Immunocompromised state and intravenous drug use are the 2 most common causes of endogenous endophthalmitis due to molds fungi. Aspergillus, Fusarium, and Scedosporium are the common organisms in mold endophthalmitis. We report a case of Fusarium endophthalmitis in a patient with uncontrolled diabetes. While diabetes mellitus is a well-known risk factor for endogenous endophthalmitis, we did not find any reported case of Fusarium endophthalmitis in a case of diabetes mellitus. The patient presented with granulomatous uveitis masquerading as noninfectious uveitis with a very good response to steroids. The characteristic clinical features were established late in the clinical course associated with poor outcome. This case highlights the significance of uncontrolled diabetes as a risk factor for Fusarium endophthalmitis and also the presentation of endophthalmitis as a masquerade syndrome. The clinician should have high index of suspicion as these cases have poor outcomes.